Target orientation of the state support and protection in competition sphere - Корчак, Наталія Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In article the social, economic and legal purposes of the state support and protection in competitionsphere are analysed.